Evaluating the effectiveness of intervention on professional and pedagogical skills among prospective physics teachers - Kusumaningtyas, Dian Artha; Sukarelawan, Moh. Irma; Adhantoro, Muhammad Syahriandi; Saputra, Wahyu Nanda Eka (Institute of Advanced Engineering and Science, 2025)
This study evaluates the effectiveness of a targeted intervention designed to enhance the professional and pedagogical skills of prospective physics teachers, addressing a key gap in teacher education. The research involved an experimental group that received the intervention and a control group that did not. The research subjects in the experimental and control groups were 120 each. To rigorously assess the impact, Whitney and Wilcoxon’s statistical tests were employed to compare pretest and posttest outcomes. Additionally, Wright map analysis was used to visualizes kill development. The results revealed a significant improvement in the professional and pedagogical skills of the experimental group compared to the control group, as indicated by Mann-Whitney test (U=1274.500, p<0.05 and U=421.500, p<0.05). The Wright map analysis further demonstrated that the experimental group experienced more consistent and substantial gains in pedagogical skills. This study contributes to the field by demonstrating the effectiveness of interventions in improving the skills of prospective physics teachers, offering educational policy recommendations, and filling important gaps in the literature. Moreover, it emphasizes the critical role of ongoing evaluation in the continuous development of teacher training programs. By addressing these areas, this research provides valuable insights that can inform the design and implementation of more effective teacher training strategies.